Valorisation of Glycerol as Renewable Feedstock: Comparison of the Exploration of Chemical Transformation Methods Aided by High Throughput Experimentation - Bohmer, Natalia; Roussiere, Thomas; Kuba, Martin; A. Schunk, Stephan (Combinatorial Chemistry & High Throughput Screening, 2012)
Renewable feedstocks have been in the spotlight of intensive research activities over the past 10 years. Glycerol is one of the feedstock molecules which has been the target of numerous research efforts, for a number of reasons. First of all glycerol is currently readily available due to the fact that it is a couple product of the first generation biodiesel production. Secondly glycerol can be taken as a representative model substrate to explore the options of selective conversion of sugar alcohols to products of value. In our paper we discuss potential routes for the valorisation of glycerol which lead to intermediates already established within the petrochemical value chain and illustrate what impact high throughput experimentation may have as a success factor on research and development for this field. As illustrative examples we have chosen the oxidative transformation of glycerol to acrolein and acrylic acid and the carbonylation of glycerol to C4-acids
Keywords: by-products